2014
DOI: 10.12965/jer.140160
|View full text |Cite
|
Sign up to set email alerts
|

The effect of weight loss by ketogenic diet on the body composition, performance-related physical fitness factors and cytokines of Taekwondo athletes

Abstract: The purpose of this study was to investigate the effects of the weight loss through 3 weeks of ketogenic diet on performance-related physical fitness and inflammatory cytokines in Taekwondo athletes. The subjects selected for this research were 20 Taekwondo athletes of the high schools who participated in a summer camp training program. The subjects were randomly assigned to 2 groups, 10 subjects to each group: the ketogenic diet (KD) group and the non-ketogenic diet (NKD) group. Body composition, performance-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(84 citation statements)
references
References 22 publications
3
79
0
2
Order By: Relevance
“…Thus, additional human trials are needed. Three weeks of a KD in humans has been shown to reduce OS resulting from caloric restriction and exercise as previously found in Taekwondo athletes . Rhyu and Cho also reported attenuated elevations in TNF‐α during a weight loss program associated with a KD; though, these data are not entirely comparable since a change in body mass and/or body composition likely effects circulating cytokine levels.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Thus, additional human trials are needed. Three weeks of a KD in humans has been shown to reduce OS resulting from caloric restriction and exercise as previously found in Taekwondo athletes . Rhyu and Cho also reported attenuated elevations in TNF‐α during a weight loss program associated with a KD; though, these data are not entirely comparable since a change in body mass and/or body composition likely effects circulating cytokine levels.…”
Section: Discussionmentioning
confidence: 64%
“…Three weeks of a KD in humans has been shown to reduce OS resulting from caloric restriction and exercise as previously found in Taekwondo athletes. 25 Rhyu and Cho also reported attenuated elevations in TNF-α during a weight loss program associated with a KD 25 ; though, these data are not entirely comparable since a change in body mass and/or body composition likely effects circulating cytokine levels. Further, 14 days of a KD has also been shown to increase blood antioxidant status in active, healthy women in response to a caloric restricted intervention.…”
Section: Discussionmentioning
confidence: 97%
“…Given that LCs dramatically restrict the energy intake from carbohydrate, which could accelerate the exhaustion of glycogen content to provide energy during exercise, high-intensity exercise performance during LCs may be particularly impaired Nutrients 2020, 12, 442 3 of 13 as carbohydrate is the dominant energy source [31,32]. Additionally, some studies revealed that metabolic adaption to ketosis resulting from LCs may exert positive influences on maintaining or even improving exercise performance [33,34], because a more durable energy source was obtained through the enhanced fat-utilization ability [32] that can help in sparing the limited glycogen storage [35]. Supposedly, an acute bout of HIIT under LC conditions could be more demanding for overweight individuals to perform, and thus they may perceive HIIT to be less enjoyable than an acute bout of MICT under LC conditions since the body still relies heavily on carbohydrate to generate energy.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-over study revealed that after 4 weeks of a LCHF diet, body weight and fat mass were significantly decreased in well-trained offroad cyclists (Zajac et al, 2014). Consuming a hypocaloric LCHF or HCLF diet for 3 weeks resulted in similar decreases in body weight and fat mass in high school taekwondo athletes (Rhyu and Cho, 2014). …”
Section: Lchf Diet and Body Compositionmentioning
confidence: 96%
“…In another study, combining a LCHF diet for 3 weeks with a 25% energy restriction resulted in the loss in lean body mass and impairment in anaerobic performance measured by the Wingate test in high school taekwondo athletes (Rhyu and Cho, 2014). It is noteworthy that performance requiring greater endurance capacity such as a 2000 m sprint, and a fatigue index in the Wingate test were actually increased in the LCHF group.…”
Section: Lchf Diet Effect On High-intensity Exercisementioning
confidence: 99%